2017
DOI: 10.1007/s11218-017-9400-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ academic judgments of overweight students

Abstract: Overweight children in schools can become victims of stereotyping and discrimination from both peers and teachers. Research on stereotypical expectations and impression and judgment formation has suggested that teachers might rely on their negative stereotypical expectations when judging students. In the present study, we experimentally investigated whether pre-service academic subject teachers' judgments about students were biased through stereotypical expectations about students' weights. Pre-service teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Hence, it would be very interesting to replicate this study using vignettes about female students. We do not know whether our results can also be generalized to other subjects because other scholars have found that preservice teachers generally hold positive stereotypical beliefs about the academic and social competences of overweight students (Müller et al, 2017). In school contexts, weight-based discrimination may therefore not be generally accepted; teachers may be more vulnerable to weight-based discriminatory beliefs and behavior when they teach physical (and not academic) competences.…”
Section: Limitationsmentioning
confidence: 72%
See 1 more Smart Citation
“…Hence, it would be very interesting to replicate this study using vignettes about female students. We do not know whether our results can also be generalized to other subjects because other scholars have found that preservice teachers generally hold positive stereotypical beliefs about the academic and social competences of overweight students (Müller et al, 2017). In school contexts, weight-based discrimination may therefore not be generally accepted; teachers may be more vulnerable to weight-based discriminatory beliefs and behavior when they teach physical (and not academic) competences.…”
Section: Limitationsmentioning
confidence: 72%
“…This could be particularly relevant in school contexts: Whereas teachers consider it highly inadmissible to discriminate against students on the basis of social class, teachers may nonetheless disadvantage nonprivileged children by means of their socially more accepted weight-based prejudices and discriminatory behavior. This may seem more likely in physical education, but also with respect to studies such as the one by Müller et al (2017), it is important to ask whether social class played a moderating role and whether the positive judgment of overweight students applied more to middle-class students than to working class students. In order to better assess the extent to which overweight is associated with disadvantages in school, future studies should therefore take a closer look at the links between overweight and other social categories.…”
Section: Limitationsmentioning
confidence: 99%